A CORRELATIONAL STUDY: SELF-EFFICACY, LEARNING STRATEGIES AND STUDENTS’ DESCRIPTIVE WRITING PERFORMANCE - Hedyan Putra; Mansye Sekewael; Hindri Febri (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
This study investigated the relationship between students’ self-efficacy, learning strategies, and descriptive writing performance in an English as a Foreign Language (EFL) context. Conducted with 103 third-semester accounting students at the State Polytechnic of Ambon during the 2024/2025 academic year, the research employed a quantitative correlational design using purposive sampling. Data were collected through a writing self-efficacy questionnaire, a writing learning strategies questionnaire, and a rubric-based descriptive writing test. The instruments were validated and demonstrated high reliability (α = 0.91 and α = 0.88), with writing performance assessed through inter-rater scoring (Cohen’s Kappa = 0.85). Data analysis involved descriptive statistics, Pearson correlation, and multiple regression. Results revealed that while most students reported high self-efficacy and moderate use of learning strategies, their writing performance remained basic (A2 based on CEFR proficiency levels). Significant positive correlations were found between self-efficacy, learning strategies—particularly cognitive and metacognitive—and writing performance, though the overall contribution of these variables accounted for only 6.4% of performance variance. The findings highlight the need for instructional practices that integrate self-regulated strategies and scaffold writing development to bridge the gap between confidence and competence.